2015
DOI: 10.1021/acs.biochem.5b00330
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the Electronic Properties of Shewanella oneidensis Cytochrome c Nitrite Reductase (ccNiR) and Its Structure: Effects of Heme Oxidation State and Active Site Ligation

Abstract: The electrochemical properties of Shewanella oneidensis cytochrome c nitrite reductase (ccNiR), a homodimer that contains 5 hemes per protomer, were investigated by UV/Visible and EPR spectropotentiometries. Global analysis of the UV/Vis spectropotentiometric results yielded highly reproducible values for the heme midpoint potentials. These midpoint potential values were then assigned to specific hemes in each protomer (as defined in previous X-Ray diffraction studies) by comparing the EPR and UV/Vis spectropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 41 publications
(199 reference statements)
5
42
1
Order By: Relevance
“…In the presence of CN − , the cathodic peak current obtained for the c c NiR-modified PGE showed a drastic decrease bellow the non-catalytic current, accompanied by a + 90 mV shift in the peak potential. A similar shift (+70 mV) was observed in non-turnover conditions for the c c NiR from Shewanella oneidensis , which was attributed to the binding of the ligand to the penta-coordinated catalytic heme 35 . It was also reported that the binding event of CN − to the c c NiR from Escherichia coli resulted in a decrease in catalytic current and a displacement of the peak potential towards more positive values 26 .…”
Section: Resultssupporting
confidence: 70%
“…In the presence of CN − , the cathodic peak current obtained for the c c NiR-modified PGE showed a drastic decrease bellow the non-catalytic current, accompanied by a + 90 mV shift in the peak potential. A similar shift (+70 mV) was observed in non-turnover conditions for the c c NiR from Shewanella oneidensis , which was attributed to the binding of the ligand to the penta-coordinated catalytic heme 35 . It was also reported that the binding event of CN − to the c c NiR from Escherichia coli resulted in a decrease in catalytic current and a displacement of the peak potential towards more positive values 26 .…”
Section: Resultssupporting
confidence: 70%
“…This feature, together with the peak at g = 3.33 and trough at g = 2.83, has been attributed to the S = 5 / 2 heme 1, weakly exchange-coupled with one or more of the nearby low-spin hemes (S = 1 / 2 ). 11,16,43,47,48 The high-spin signal provides an excellent spectroscopic handle for the active site, and titration of ccNiR by nitrite was followed by monitoring its disappearance as nitrite was added. A spectrum was obtained at each nitrite concentration, and in each case the spectrum obtained in the presence of 6 mM nitrite (Figure 2b) was subtracted from it, to generate a difference spectrum analogous to that of Figure 2c.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This is much higher than the midpoint potential obtained for the first reduction step of S. oneidensis ccNiR in the absence of strongfield ligands and much higher even than that obtained in the presence of the strong-field ligand cyanide (20 mV vs NHE). 16 Singular value decomposition (SVD) analysis 16,51,52 and the presence of tight isosbestic points at 341 and 415.5 nm in Figure 4a reveal only a single spectral component attributable to c-heme reduction.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…The SO , acted as weak inhibitors in the activity assay [156]. Azide, N 3 − , was expected to bind to the active site heme iron as a competitive inhibitor [181,182] just like SO 4 2− . However, the structure of the NrfAws-N 3 − complex (2.0 Å resolution) revealed a water bound to Fe at 2.05 Å, and in close proximity the N 3 − anion, bound to residues lining Fig.…”
Section: Active Sitementioning
confidence: 99%
“…As expected both SO 4 2− , and structurally related PO 4 3− , acted as weak inhibitors in the activity assay [ 156 ]. Azide, N 3 − , was expected to bind to the active site heme iron as a competitive inhibitor [ 181 , 182 ] just like SO 4 2− . However, the structure of the NrfAws-N 3 − complex (2.0 Å resolution) revealed a water bound to Fe at 2.05 Å, and in close proximity the N 3 − anion, bound to residues lining the active site entrance, with hydrogen bonds to Gln 276 (3.0 Å), Tyr 218 (2.8 Å) and two hydrogen bonds to Arg 114.…”
Section: Structure Of Pentaheme Cytochrome C Nitri...mentioning
confidence: 99%